Implementasi Sistem Informasi Untuk Manajemen Pengolahan Bank Sampah Organik Dan Sampah Non Organik - Eni Heni Hermaliani; Mochammad Andre; Muhamad Al Akbar; Sunandar Adityo; Riyan Latifahul Hasanah (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Community participation in reducing the quantity or volume of waste as well as managing waste is one of the most important parts in tackling the waste problem, especially in big cities. Reduction or reduction in the amount and volume of waste is an effort made to minimize the presence of waste. The waste bank is a means for the community that is used to manage waste that has economic value. In the residential area of Villa Pertiwi Block P Rt.004 Rw.015, Sukamaju Village, Cilodong District, Depok. In the process of processing and storing waste bank customer data, they still use the manual method, namely by recording every transaction into a book, so that problems often arise such as damaged or lost data, data duplication, and report books that are left more and more and accumulate. Therefore, by implementing training and implementing and using a web-based waste bank application system, it can make it easier to process and store customer data in the operational activities of the waste bank. Customers can register as waste bank customers through the waste bank information system, making it easier to validate data and recap customer data collection, admins can print deposit data reports from customers' waste bank results.